Extranasopharyngeal angiofibroma in an adolescent male: a case report - Arulappan, Lourdes Albina Siluvai (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
A 16 year old male presented with complaints of obstruction in the right side of nose for 15 days, 4 episodes of unprovoked bleeding from right nasal cavity for one week. The epistaxis was sudden in onset. CT revealed polypoidal mass in the right nasal cavity, filling inferior 1/3rd of the right anterior nasal cavity, with attachment to the nasal septum. Endoscopic excision of the mass was done in toto and histopathological examination report showed it to be an extra nasopharyngeal angiofibroma.